Mobile embedded system: Your door key evolved with your smartphone - A user evaluation of a two-factor authentication - Teh, P.; Ling, Huo Chong; Cheong, S.; Ahmed, P. (2015)
© 2016, IGI Global. The use of smartphone is pervasive. With device pocketability driving user engagement throughout the day, it is highly probable that smartphones will replace daily items (e.g., keys and credit cards) that people now carry around. The idea presented here is a significant step in this direction. This chapter details the authors' design and development of a smartphone access control system using Near Field Communication (NFC) Encrypted Steganography Graphical Password (ESGP). The primary objective is to leverage the technical capability of NFC-enabled smartphones in developing a two-factor authentication system connecting physical resources (i.e., premises) and virtual resources (i.e., password knowledge). This involves a novel integration of token-based, graphical-password authentication, cryptography and steganography. The second objective is to evaluate users' behavior intention to use the system. New insights for researchers and business world interested in the unified solutions for NFCcompatible smartphone, access control and mobile security are provided.